Peningkatan Kebersihan Gigi dan Mulut Melalui Edukasi Frekuensi Menyikat Gigi pada Siswa Sekolah Dasar - Arfiah Jauharuddin; Fidzah Nurfajrina Murad; Dewi Sartika; Suciyati Sundu; Rumaisha Soumena (Lembaga Pengembangan Kinerja Dosen, 2024)
Oral hygiene is an important factor in maintaining children's health, especially in elementary school age. This study aims to measure the effectiveness of education on tooth brushing frequency in improving oral hygiene in elementary school students. This study involved 50 students from grades 4 and 5 at Sekolah Dasar Inpres Batua 1 who were given educational interventions on the importance of brushing their teeth twice a day, correct brushing techniques, and the use of fluoride-containing toothpaste. Measurements were made using plaque index before and after the intervention. The results showed a significant decrease in the average plaque index of students from 2.5 before education to 1.2 after education, with an increase in dental hygiene of 52%. In addition, the number of students who brushed their teeth twice a day increased from 40% to 90%, and students with a plaque index <2 increased from 20% to 70%. These results indicate that the education provided is effective in increasing awareness and good brushing habits among elementary school students. This study concludes that the educational intervention on tooth brushing frequency can significantly improve dental hygiene in elementary school students.